Pengaruh Pembiayaan Jual Beli Dan Pembiayaan Bagi Hasil Terhadap Kinerja Keuangan Bank Syariah - Alfajri Khairul Ihsan (Jurnal Kajian Islam dan Sosial Keagamaan, 2023)
Competition between banks in Indonesia is getting tougher, which will directly or indirectly affect the achievement of bank profitability, including Islamic banks, which have recently been in demand by many customers because there are no interest rates but apply profit sharing, Islamic banks prove to be institutions that can survive in the midst of worsening economic crisis. The object of research is Islamic banking companies listed on the Indonesia Stock Exchange (IDX) in the period 2017 to 2020. Statistical calculation techniques can be performed using descriptive statistics, multiple linear regression analysis, classical assumption tests and hypothesis testing. Analysis of the data obtained is then processed with the help of computer technology, namely Microsoft Excel and SPSS (Statistical Product and Service Solution) software. simultaneously on Financial Performance. Suggestions The next researcher is advised to use Islamic Commercial Banks in Indonesia so that there are more comparisons and can better assess how influential financing is on financial performance. Further researchers are advised to add the independent variables from this study with other variables that are allegedly able to affect the Financial Performance of Islamic Banks. Thus the expected results are more accurate